2017
DOI: 10.2147/dddt.s139837
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of direct-acting antiviral therapy in previous hard-to-treat patients with recurrent hepatitis C virus infection after liver transplantation: a real-world cohort

Abstract: BackgroundRecurrent hepatitis C virus (HCV) infection after liver transplantation (LT) has been a frequent and relevant problem in the past two decades. This analysis evaluated the efficacy and safety of new interferon (IFN)-free direct-acting antiviral (DAA) therapies in a large real-world cohort of HCV patients after LT.MethodsWe retrospectively analyzed a cohort of 157 patients infected with HCV who underwent deceased donor LT between 1997 and 2014. Patient survival, outcome, and side effects of antiviral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Some reports suggest that all patients, irrespective of their HCV genotype, should be treated immediately after LT to prevent recurrent hepatitis C and fibrosis progression in the graft [19, 20]. Our results of high tolerability of DAAs also in the peri-LT period supports continuing the DAA therapy, started while patients are on the waiting list, also in the immediate post-LT period.…”
Section: Discussionsupporting
confidence: 68%
“…Some reports suggest that all patients, irrespective of their HCV genotype, should be treated immediately after LT to prevent recurrent hepatitis C and fibrosis progression in the graft [19, 20]. Our results of high tolerability of DAAs also in the peri-LT period supports continuing the DAA therapy, started while patients are on the waiting list, also in the immediate post-LT period.…”
Section: Discussionsupporting
confidence: 68%
“…[23][24][25] For example, some recommended DAA treatment deferral (ie at least 4-6 months) following potentially curative HCC management. [26][27][28][29] Third, the DAA response among patients with HCC is relevant, particularly in relation to optimum timing of initiation. In two cohort studies conducted in the United States, the virological response to DAA therapy was impaired in HCV-related HCC patients, compared to the non-HCC population.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in response to the controversy around HCC recurrence risk, the timing of DAA therapy in relation to HCC management became a point of debate . For example, some recommended DAA treatment deferral (ie at least 4‐6 months) following potentially curative HCC management . Third, the DAA response among patients with HCC is relevant, particularly in relation to optimum timing of initiation.…”
Section: Introductionmentioning
confidence: 99%
“…9 The previously mentioned Australian TOSCAR cohort found that a baseline MELD ≥19.5 was associated with an increased need for rescue transplantation after HCV treatment. 5 This was echoed in findings from the European ELITA cohort, which found that 95% of patients with decompensated HCV cirrhosis and a MELD greater than 20 still needed a liver transplant after treatment. This cohort also found an increased risk for needing early liver transplant and a significant risk for death before and after liver transplant.…”
Section: Safety Issues In Patients With Decompensated Cirrhosismentioning
confidence: 99%
“…Furthermore, only one‐third of patients in SOLAR‐2 and less than 5% of patients in ASTRAL‐4 had decompensated cirrhosis. The TOSCAR cohort enrolled patients with decompensated hepatitis C cirrhosis (MELD score ≥15, CTP B or C) and reported a SVR12 rate of only 70% after 24 weeks of therapy with DAC and SOF . Although the mechanistic reasons for these decreased SVR12 rates are not known, they may be related to impaired intestinal drug absorption in the setting of portal hypertension and decreased hepatic drug delivery caused by capillarization of the cirrhotic liver.…”
Section: Treatment Effectiveness In Patients With Decompensated Cirrhmentioning
confidence: 99%